Silver from the North - Johannes Heinrichs (Karanos, 2024)
Following Strabo, the mines at Damastion and in its wider region have traditionally been localized in western Illyria. But for several reasons the only known ancient silver mine, west of the Axios, in the Openika hills up modern Ohrid, is no option. Findspots of coins of the Damastion type, minted after the Chalkidian model, however hint at the wider Skupi/Skopje basin as an area of circulation and as a center of silver commerce. Two ancient mining districts can be located not far off, to its east and north, in the regions of Kratovo (in modern North Macedonia) and (somewhat later) Ulpianum (in Kosovo or southern Serbia). From both districts, in the first half of the 4th c., mineral silver travelled south via the Axios Valley and the Anthemous region to the federal Chalkidian mint at Olynthos. The mines in the Kratovo district bordered on Hellenized Paionia, whereas those in the north, belonging to Dardania, were far less in touch with Greek civilization. Damastion’s location, probably in the Paionian borderlands, accounts for the Greek character of its coins. They became models for those from Dardanian mines which, however, soon fell off Greek standards. Nonetheless, Damastion kept close connections with the Chalkidians: soon after the Peloponnesian War it had been founded by the Mendaians and other groups including refugees from Aigina. Chalkidian economic connections with the Dardanian north, based on silver trade, were an impulse for a defensive alliance that the Illyro-Dardanian king Grabos concluded around 357 with the Chalkidians against Philip. Extremely short-lived, it was cancelled by the Olynthians when they accepted Philip’s offer of a symmachy. They threw the stele inscribed with their Dardanian alliance into a river flowing by their city even before it was fully incised.